European Painting and World War I: Evolution of Modern Era and Beyond - Abir, Md. Shazed Ul Hoq Khan (EAST WEST JOURNAL OF HUMANITIES, 2017)
World War I, famously known as The Great War, had an immense impact globally. It changed not only the geopolitical equations and alliances among countries but also reshaped both the history and future of modern art and culture worldwide. European painting, having its grand legacy of almost three thousand years (from seven century BC till today) went through a drastic change in its form and focus during this war. Artists changed their way of interpreting the world around as well as their artistic expression. They could no longer express their emotions and views as glibly through their paintings/art works as they did during the romantic or Victorian era, just the period prior to the Great War. Images they produced were mostly fragmented and distorted. This paper focuses on how the trauma and havoc of the Great War affected European painters and their paintings with the formation of various “Isms”, which developed new wave of modern painting accordingly. “Things fall apart; the centre cannot hold; Mere anarchy is loosed upon the world, The blood-dimmed tide is loosed, and everywhere The ceremony of innocence is drowned;” (Yeats, 1919)